Effects of intrathecal administration of sodium nitroprusside and nicardipine on cerebral pial microcirculation, cortical tissue oxygenation, and electrocortical activity in the early post-resuscitation period in a porcine cardiac arrest model. - Hyoung Youn Lee; Najmiddin Mamadjonov; Kyung Woon Jeung; Yong Hun Jung; Wan Young Heo; Yong Soo Cho; Byung Kook Lee; Tag Heo (PLoS ONE)
Recent studies suggested intrathecal vasodilator administration as a therapy to mitigate post-ischemic cerebral hypoperfusion following cardiac arrest. We examined the effects of two commonly used intrathecal vasodilators, sodium nitroprusside (SNP) and nicardipine, on cerebral pial microcirculation, cortical tissue oxygen tension (PctO2), and electrocortical activity in the early post-resuscitation period using a porcine model of cardiac arrest. Thirty pigs were resuscitated after 14 min of untreated cardiac arrest. At 30 min after resuscitation from cardiac arrest, 30 pigs randomly received 4 mg of SNP, 4 mg of nicardipine, or saline placebo via subdural intracranial catheters and were observed for 5 h. Group effect and group-time interaction were assessed using linear mixed-effects models. The mean arterial pressure was lower in the nicardipine group (coefficient [95% confidence interval CI], -15.824 [-24.082 to -7.566]) and higher in the SNP group (coefficient [95%CI], 11.232 [2.974-19.490]) compared to the saline group. The percentage of pial arteriole diameter relative to the pre-arrest baseline value (coefficient [95% CI], 48.970 [13.884-84.057]), microvascular flow index (coefficient [95% CI], 0.296 [0.071-0.521]), and PctO2 (coefficient [95% CI], 26.926 [12.404-41.449]) were higher in the SNP group but not in the nicardipine group compared to the saline group. Amplitude-integrated electroencephalography amplitude recovery was faster in the SNP group (coefficient [95% CI], 1.149 [0.468-1.829]) but not in the nicardipine group compared to the saline group. In conclusion, intrathecal SNP but not nicardipine was effective in treating post-ischemic cerebral hypoperfusion after cardiac arrest.